Feature Papers in Eng 2022 - Gil Bravo, Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The aim of this second Eng Special Issue is to collect experimental and theoretical re-search relating to engineering science and technology. The general topics of Eng are as follows: electrical, electronic and information engineering; chemical and materials engineering; energy engineering; mechanical and automotive engineering; industrial and manufacturing engineering; civil and structural engineering; aerospace engineering; biomedical engineering; geotechnical engineering and engineering geology; and ocean and environmental engineering. Therefore, the following editorial is a selection of representative works of these topics.